The Effect of Stressors and Coping Strategies on Elderly Quality of Life during the Covid-19 Pandemic: The Effect of Stressors and Coping Strategies on Elderly Quality of Life during the Covid-19 Pandemic - Reza Wahyuni; Diah Krisnatuti; Musthofa (Journal of Family Sciences, 2022)
The Covid-19 pandemic has had an impact on people's lives, especially for the elderly who are at high risk of contracting and can cause death. The purpose of this study was to determine the effect of stressors and coping strategies on the quality of life of the elderly. This research was conducted all over Indonesia, from April until June 2021, by using a cross-sectional study method, and the sample criteria involved 50 elderly men and 50 elderly women aged 60 years and over who were obtained by quota sampling method. This research uses descriptive, correlation and regression analysis. The results showed that stressors for elderly men and women are in a low category, coping strategies, and quality of life for elderly men and women are in the moderate category. The correlation test showed that the lower self and environment stressors and the higher emotion-focused coping, the higher quality of life of the elderly. The regression test showed that the use of emotion-focused coping affects high quality of life of the elderly. The quality of life of the elderly can be improved by increasing the use of emotion-focused coping. Understanding the concept of stressors, coping strategies and the quality of life of the elderly during the Covid-19 pandemic are important to help the elderly living their life well during Covid-19 pandemic.